(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aims to identify the role of the Heritage Commission’s digital media activities in developing cultural identity among the Saudi public. The study is a descriptive study, relying on a media survey approach. The study sample consisted of (300) male and female users of the Saudi Heritage Commission’s digital media activities. A questionnaire was used as a data collection tool. The study reached a number of results, the most prominent of which are: Saudi respondents believe that the Commission’s account on X was the most preferred digital media outlet for the Heritage Commission, with a percentage of 34%. The Commission’s official website came in second place, with a percentage of 30.3%, followed by the Commission’s Instagram account, which came in third place, with a percentage of 28.7%. The motive "to learn about heritage-related activities" topped the list of motivations for the Saudi audience in the study sample to use the Saudi Heritage Commission’s online media, with an arithmetic mean of 2.60. In second place came the motive "to learn about the Kingdom’s cultural wealth and archaeological sites," with an average of 2.40, followed by the motive "to learn new information," with an average of 2.22. The phrase "The Kingdom has many antiquities within its borders" topped the Saudi audience’s views on aspects of cultural identity presented in the Heritage Commission’s digital media activities, with an arithmetic mean of 2.64. In second place came the phrase "The Kingdom has a history of oral traditions, social practices, rituals, and festive occasions," with an average of 2.55, followed by the phrase "There are antiquities belonging to the Kingdom in maritime areas under its sovereignty," with an average of 2.54. Saudi respondents believe that the digital media activities of the Heritage Commission contribute significantly to increasing their level of cultural identity, ranking first with a percentage of 86%.